A ventricular fibrillation cardiac arrest model with extracorporeal cardiopulmonary resuscitation in rats: 8 minutes arrest time leads to increased myocardial damage but does not increase neuronal damage compared to 6 minutes - Stommel, Alexandra-Maria; Högler, Sandra; Mueller, Matthias; Magnet, Ingrid Anna Maria; Kodajova, Petra; Ullram, Benjamin; Szinovatz, Alexander; Panzer, Felix Paul; Engenhart-Seyrl, Anna; Kaschmekat, Julia; Schütz, Tamara; Holzer, Michael; et al. (Frontiers in Veterinary Science, 2023)
Introduction: Extracorporeal cardiopulmonary resuscitation (ECPR) is an emerging strategy in highly selected patients with refractory cardiac arrest (CA). Animal models can help to identify new therapeutic strategies to improve neurological outcome and cardiac function after global ischemia in CA. Aim of the study was to establish a reproducible ECPR rat model of ventricular fibrillation CA (VFCA) that leads to consistent neuronal damage with acceptable long-term survival rates, which can be used for future research.Male Sprague Dawley rats were resuscitated with ECPR from 6 min (n=15) and 8 min (n=16) VFCA. Animals surviving for 14 days after return of spontaneous resuscitation (ROSC) were compared with sham operated animals (n=10); neurological outcome was assessed daily until day 14. In the hippocampal cornu ammonis 1 region viable neurons were counted. Microglia and astrocyte reaction was assessed by Iba1 and GFAP immunohistochemistry, and collagen fibers in the myocardium were detected in Azan staining. QuPath was applied for quantification.Results: Of the 15 rats included in the 6 min CA group, all achieved ROSC (100%) and 10 (67%) survived to 14 days; in the 8 min CA group, 15 (94%) achieved ROSC and 5 (31%) reached the endpoint. All sham animals (n=10) survived two weeks. The quantity of viable neurons was significantly decreased, while the area displaying Iba1 and GFAP positive pixels was significantly increased in the hippocampus across both groups that experienced CA. Interestingly, there was no 2 This is a provisional file, not the final typeset article difference between the two CA groups regarding these changes. The myocardium in the 8 min CA group exhibited significantly more collagen fibers compared to the sham animals, without differences between 6 and 8 min CA groups. However, this significant increase was not observed in the 6 min CA group.Our findings indicate a uniform occurrence of neuronal damage in the hippocampus across both CA groups. However, there was a decrease in survival following 8-min CA. Consequently, 6 min CA resulted in predictable neurological damage without significant cardiac damage and ensured adequate survival rates up to 14 days. This appears to offer a reliable model for investigating neuroprotective therapies.